Criminalization Policy in Realizing of Rupiah Sovereignty - Dwiki Oktobrian (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Sovereignty of the Rupiah is mandatory or grand design in Law Number 7 Year 2011 on The Currency, sovereignty of the Rupiah has resulted in the obligation to use Rupiah within the territory of the Republic of Indonesia in every payment transaction or business obligations. Every act that violates this obligation is responded by the law with punishment, while the times show that there are more acts of not using the Rupiah which not only occur in border areas but also in ordinary urban areas. This article discusses how the urgency of criminalization of Rupiah protection and how criminalization was formulated. The discussion is carried out with a normative approach to provide an overview of how criminalization was formulated in a law. The conclusion is that the use of the criminalization policy has urgency to protect the sovereignty of the Rupiah because actions that attack could result in economic instability which create various other types of criminal acts. Even so, the criminalization policy has not been formulated effectively because the details of the prohibited acts are too simple so that it creates interpretive bias, especially the ultimum remedium principle is not formulated so it is worrief that the formulation will contribute overcapacity in prison